Causal relationship between the gut microbiota, immune cells, and coronary heart disease: a mediated Mendelian randomization analysis - Yang, Feifei; Song, Hui; Tang, Weizhi; Liu, Lingyun; Zhu, Ziyi; Ouyang, Bin; Zhang, Liwen; He, Guixin; Qin, Weibin (Frontiers in Microbiology, 2024)
Background: Recent studies have shown that gut microbiota (GM), immune cells, and coron ary heart disease (CHD) are closely related, but the causal nature is largely unknown. This s tudy aimed to investigate this causal relationship and to reveal the effect of GM, immune ce lls on the risk of developing CHD using mediated Mendelian randomization (MR) analysis.Methods: Firstly, we looked for the data related to GM, immune cells, and CHD through p ublished genome-wide association studies (GWAS), filtered the SNPs (single nucleotide polym orphisms) related to GM and immune cells, and then performed the first MR analysis to get the disease-associated intestinal bacteria and disease-associated immune cells. Then, three M R analyses were performed: disease-associated GM to disease-associated immune cells, disease -associated immune cells to disease, and disease-associated GM to disease. Each MR analysis was performed using inverse variance weighting (IVW), MR-Egger regression, weighted med ian, weighted models, and simple models.Results: 6 GM and 25 immune cells were associated with CHD. P < 0.05 and OR > 1 for the IVW method in the MR analysis of g__Desulfovibrio.s__Desulfovibrio_piger to EM DN (CD4-CD8-) %T cell, P < 0.05 and OR < 1 for the IVW method in the MR analysis of E M DN (CD4-CD8-) %T cell to CHD, and P < 0.05 and OR < 1 for the IVW method in t he MR analysis of g__Desulfovibrio.s__Desulfovibrio_piger to CHD.An increase in the amount of g__Desulfovibrio.s__Desulfovibrio_piger leads to a n increase in the amount of EM DN (CD4-CD8-) %T cell and an increase in the amount o f EM DN (CD4-CD8-) %T cell reduces the risk of developing CHD. Our study provides so me reference for reducing the incidence of coronary heart disease by regulating GM and im mune cells.